2020
DOI: 10.3390/ijerph17165706
|View full text |Cite
|
Sign up to set email alerts
|

“Moving Forward with Life”: Acceptability of a Brief Alcohol Reduction Intervention for People Receiving Antiretroviral Therapy in South Africa

Abstract: Background: In South Africa, interventions are needed to address the impact of hazardous drinking on antiretroviral therapy among people living with HIV (PLWH). Participant feedback about these interventions can identify ways to enhance their acceptability. We interviewed participants in a randomized controlled trial of a brief motivational interviewing and problem-solving therapy (MI-PST) intervention about their perceptions of this alcohol-reduction intervention. Methods: The trial was conducted in HIV treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Integrating AOD treatment into HIV care can improve ART adherence, yet this is not typically routine practice in SA or other low-resource settings [15][16][17]. Furthermore, ART adherence interventions are rarely adapted for AODa missed opportunity for maximizing HIV treatment outcomes [18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…Integrating AOD treatment into HIV care can improve ART adherence, yet this is not typically routine practice in SA or other low-resource settings [15][16][17]. Furthermore, ART adherence interventions are rarely adapted for AODa missed opportunity for maximizing HIV treatment outcomes [18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…Ultimately, 35 full-text articles were included in this review. Several relevant protocol [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], baseline or pilot [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], and feasibility studies [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] were identified; however, they did not meet the inclusion criteria because trial outcomes were the focus of this review.…”
Section: Methodsmentioning
confidence: 99%
“…Among patients with diabetes, combining information provision, MI techniques, and meaningful relationships led to improved sense of control [30], while others reported that it drove optimism [31]. Provision of information combined with MI techniques was also identified as two intervention components perceived as most beneficial in people receiving antiretroviral therapy [32]. Consistent with this, our study shows that the availability of tailored, accurate, up-to-date, and complete information on how to cope with AET-related issues as well as breast cancer women's involvement in care, coupled with the ongoing, timely support from nurse navigators, created synergies that were perceived to grow women's empowerment and optimism for the long-term intake of AET.…”
Section: Key Findingsmentioning
confidence: 99%